2020
DOI: 10.1093/nar/gkaa938
|View full text |Cite
|
Sign up to set email alerts
|

Complex DNA sequence readout mechanisms of the DNMT3B DNA methyltransferase

Abstract: DNA methyltransferases interact with their CpG target sites in the context of variable flanking sequences. We investigated DNA methylation by the human DNMT3B catalytic domain using substrate pools containing CpX target sites in randomized flanking context and identified combined effects of CpG recognition and flanking sequence interaction together with complex contact networks involved in balancing the interaction with different flanking sites. DNA methylation rates were more affected by flanking sequences at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Interestingly, the flanking sequence-dependent fluctuations of oxidation rates were higher on mCpA and mCpC sites than on CpG sites, suggesting that on the less active substrate, the quality of the fit of the flanking sequence to the enzyme’s preferences becomes more important. A similar observation had been made previously with DNMT3B 29 . Moreover, we observe that the CpG recognition is modulated by the flanking base pairs, as indicated by the strong preference of TET1 and TET2 for mCpA oxidation with a T at the +1 site.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the flanking sequence-dependent fluctuations of oxidation rates were higher on mCpA and mCpC sites than on CpG sites, suggesting that on the less active substrate, the quality of the fit of the flanking sequence to the enzyme’s preferences becomes more important. A similar observation had been made previously with DNMT3B 29 . Moreover, we observe that the CpG recognition is modulated by the flanking base pairs, as indicated by the strong preference of TET1 and TET2 for mCpA oxidation with a T at the +1 site.…”
Section: Resultssupporting
confidence: 87%
“…In the last 2 years novel experimental approaches have shown pronounced effects of flanking sequences on the CpG recognition of DNMT3A, DNMT3B, and DNMT1 [27][28][29] , leading to differences in the substrate preferences of both DNMT3 paralogs 27 or DNMT3A and its somatic cancer mutant R882H 26 . Mechanistically, flanking sequences can affect indirect DNA shape readout [26][27][28] , but also direct DNA contacts and alternative contact networks between the enzymes and different flanking sequences were found 27,29 . In DNMT1, striking differences in the mechanism of DNA rearrangement after base flipping were observed in different flanking contexts that were directly coupled to enzyme activity 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different DNMTs and isoforms have been reported to display different binding specificities. By structural, functional, and cellular characterization of DNMT3A and DNMT3B, a multilayered substrate-recognition mechanism was identified that accounts for their divergent genomic methylation activities [ 34 , 35 , 36 ]. Thus, the temporary change in the availability of particular DNMTs potentially contributes to the dynamic modulation of DNA methylation changes of specific genes, e.g., being associated with synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Its function, however, can be partially compensated by catalytically inactive isoforms of DNMT3B such as DNMT3B3 (Weisenberger et al, 2004;Duymich et al, 2016;Zeng et al, 2020). DNMT3A and DNMT3B have distinct mechanisms of DNA substrate engagement and show differential preference for the flanking sequence of target CpG (Handa & Jeltsch, 2005;Dukatz et al, 2020;Gao et al, 2020;Mallona et al, 2021), and we point readers to the excellent reviews of the molecular and structural basis for the catalysis of de novo methylation by DNMT3 (Jurkowska & Jeltsch, 2016;Ren et al, 2018). Furthermore, DNMT3A/B as well as DNMT3L can interact with histone tails through shared regulatory domains.…”
Section: Role Of Histone Methylation In Targeting De Novo Dnmtsmentioning
confidence: 99%